The Distribution in International Marketing - Correlation between International and Local Channels in Kosovo - Karaxha, Hidajet; Karaxha, Halit; Kristo, Ilia (European Journal of Economics and Business Studies, 2015)
Nowadays, with all these turbulent markets, the international channels are becoming more and more important. The motivation of channel members is an important characteristic in building the relations between international and local channels. The distribution channels in countries in transition can be spread and not effective. Therefore an adequate design of the firm's strategies about marketing should be responsible for the changes between distribution channels in different countries. Sometimes this can require the delegation of marketing functions beyond national affiliates in businesses activities in promoting prices and making the products available for consumers in different countries. The globalization of markets is a phenomenon that has received great attention and is being broadly debated in all levels. In every process of globalization, the distribution of products and services between and inside local industrial markets is very important. The globalization of markets and the reorganization of distribution are interdependent processes that include changes in markets structures. In enhanced national markets, kosovar companies in order to satisfy customer requirements try to specialize the distribution levels of products and services treated with increased pressure to develop a communication in countries of the region and Europe, in dissemination of information that ease the free flow of information and products in national and international borders. This paper contains empirical data that were collected through questionnaires and interviews, and secondary data as well based on reviewing the existing literature about international distribution – the correlation between national and local channels. The final compilation of the questionnaire, the methodology and the sample were realized by analyzing the determining factors that affect the distribution in international markets. The research was realized with the owners, directors, managers and other company holders in Kosovo. The methods that were used in this paper were quantitative and qualitative methods. The sample is intentional (not probable).
Keywords: international marketing, international distribution channels, the design of international channels, the motivation of the international and local channel members.